Early childhood caries predictors - Stevanović, Marko; Cvetković, Andrijana; Stošović-Kalezić, Ivana; Bukumirić, Zoran; Milojković, Zoraida; Martinović, Brankica; Stevanović, Nikola; Lazić, Dragoslav; Jovičić, Olivera; Ivanović, Mirjana (Vojnosanitetski pregled, 2021)
Background/Aim. Dental caries represents a health problem of all ages, but it is especially significant in the earliest age of children. Early childhood caries can develop immediately after the eruption of deciduous teeth, resulting in many complications, such as tooth extraction, which is reflected in the quality of life and health. Early childhood caries is influenced by a large number of predictors. Considering that the data on predictors for the development of deciduous teeth caries are scarce, the aim of this paper was to determine the prevalence of deciduous teeth caries and detect the predictors for the development of early childhood caries. Methods. Our survey included 117 children of both genders, aged 3 to 6 years, from the territory of Kosovska Mitrovica and Zvečan. All respondents, including children and parents, were surveyed, and thus general data was obtained. A dental examination was performed on all children. The current state of dental health was inserted into special research cards that were in line with the recommendations of the World Health Organization. Those predictors of dental health level that were statistically significant in models of univariate ordinal logistic regression at the significance level of 0.05 were included in the model of multivariate ordinal logistic regression. Results. According to the full structure, there were 49.6% of boys and 50.4% of girls. Healthy teeth were present in 25 (21.4%) children, 19 had reversible changes (16.2%), while 73 (62.4%) children had irreversible carious changes on teeth. The most important detected predictors were sweets consummation, sleeping with a baby bottle, 6 and more meals per day, frequent usage of medical syrups, child’s daily tooth-brushing frequency, child’s independent tooth-brushing frequency, usage of non-fluoride toothpaste, a lack of professional fluoride application, and mouth breathing. Conclusion. This research contributed to the detection of a large number of predictors that are most important for the development of early childhood caries. In order to reduce the risk of caries development, it is necessary to act in more spheres. This certainly requires planning and implementing preventive dental programs.
Keywords: child, preschool; dental caries; food and beverages; habits; oral hygiene; preventive dentistry; risk factors